2005
DOI: 10.1091/mbc.e04-07-0622
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast GTPase Mtg2p Is Required for Mitochondrial Translation and Partially Suppresses an rRNA Methyltransferase Mutant,mrm2

Abstract: The assembly of ribosomes involves the coordinated processing and modification of rRNAs with the temporal association of ribosomal proteins. This process is regulated by assembly factors such as helicases, modifying enzymes, and GTPases. In contrast to the assembly of cytoplasmic ribosomes, there is a paucity of information concerning the role of assembly proteins in the biogenesis of mitochondrial ribosomes. In this study, we demonstrate that the Saccharomyces cerevisiae GTPase Mtg2p (Yhr168wp) is essential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 55 publications
5
77
0
1
Order By: Relevance
“…While some Rmd9p-TAP sedimented into the gradient, there were no distinct peaks (our unpublished results). This result strongly indicated that Rmd9p-TAP is not a true ribosomal protein, but did not rule out a weaker ribosomal association that could be detectable at lower salt concentrations (Datta et al 2004). We therefore subjected solubilized mitochondria to gradient sedimentation under low-salt (100 mm NH 4 Cl) conditions (Figure 4).…”
Section: Isolation Of Mutations In Three Genes That Cause Synthetic Petmentioning
confidence: 97%
“…While some Rmd9p-TAP sedimented into the gradient, there were no distinct peaks (our unpublished results). This result strongly indicated that Rmd9p-TAP is not a true ribosomal protein, but did not rule out a weaker ribosomal association that could be detectable at lower salt concentrations (Datta et al 2004). We therefore subjected solubilized mitochondria to gradient sedimentation under low-salt (100 mm NH 4 Cl) conditions (Figure 4).…”
Section: Isolation Of Mutations In Three Genes That Cause Synthetic Petmentioning
confidence: 97%
“…This is probably a conserved function because in other organisms, such as V. harveyi, B. subtilis, C. crescentus, and E. coli, CgtA interacts with the 50S ribosomal subunit and has been shown to be involved in assembly or stability of the 50S subunit (17,23,27,28). Interestingly, a yeast mitochondrial CgtA homolog is essential for translation, likely through an involvement in ribosome biogenesis (29). In C. crescentus, a temperature-sensitive mutant was isolated with a defect in 50S ribosome assembly or stability, but this defect occurred at both the permissive and restrictive temperatures, indicating that this is not the essential function of CgtA (28).…”
mentioning
confidence: 99%
“…1C). In keeping with the nomenclature adopted previously for naming genes coding for GTPases that function in expression of the mitochondrial translation system (11,12), we propose MTG3 (mitochondrial GTPase) as a name for this gene.…”
Section: S]methionine Into Mitochondrial Gene Products (Not Shown) Bmentioning
confidence: 96%
“…MTG1 codes for a member of the YIqF GTPase family that has been implicated in assembly of the mitochondrial large ribosomal subunit (11). Mutations in MTG2 have also been shown to abolish mitochondrial translation (12). The product of this gene is a member of the Obg GTPase family that binds to the large ribosomal subunit and is likely to function in its assembly.…”
mentioning
confidence: 99%